The mission of women in the Church and in the world according to universal church legislation and the legislation of the Church in Poland - DYDUCH, JAN (Prawo Kanoniczne, 2017)
The Second Vatican Council set forth a teaching according to which the women’s mission of evangelization and missionary activity is a very specic one. e teaching nds its realization in the universal church legislation and the legislation of the Church in Poland. e example of the latter are the nal documents of the Second Plenary Council of the Episcopal Con- ference of Poland. Women take their part in the mission of evangelization and sanctication, as well as, in marriage and family life.